2017
DOI: 10.1002/dta.2235
|View full text |Cite
|
Sign up to set email alerts
|

Silibinin affects the pharmacokinetics of methadone in rats

Abstract: The aim of the present study was to investigate the pharmacokinetic effect of silibinin on methadone in rats. Twenty-four male Sprague-Dawley rats were randomly divided into 4 groups: control group, single dose of 100 mg/kg group, multiple doses of 100 mg/kg group, and multiple doses of 30 mg/kg group. A single dose of 6 mg/kg methadone was administrated to rats orally without or with silibinin. Plasma samples were collected via tail vein at different time points and concentrations of methadone and its metabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…In the present study, the significant alteration in MR ODV in the presence of 5 and 20 mg/kg vonoprazan suggested that vonoprazan is capable of altering the formation of ODV, which is mainly metabolized by CYP2D6. 15,20 As shown in Figure 5, while the slope of the concentration-time curve was similar in all the rats after oral administration, the coadministration of vonoprazan increased the AUC (0-t) , C max and MR ODV of VEN with a decrease in the total plasma clearance. These results indicate that vonoprazan can reduce the metabolism in the GI tract during the intestinal absorption.…”
mentioning
confidence: 78%
“…In the present study, the significant alteration in MR ODV in the presence of 5 and 20 mg/kg vonoprazan suggested that vonoprazan is capable of altering the formation of ODV, which is mainly metabolized by CYP2D6. 15,20 As shown in Figure 5, while the slope of the concentration-time curve was similar in all the rats after oral administration, the coadministration of vonoprazan increased the AUC (0-t) , C max and MR ODV of VEN with a decrease in the total plasma clearance. These results indicate that vonoprazan can reduce the metabolism in the GI tract during the intestinal absorption.…”
mentioning
confidence: 78%
“…Silibinin exhibits no harmful drug interactions at normal doses (200-900 mg/day), but at higher concentrations it can lead to clinical important drug-drug interactions through inhibition of CYP3A4 and P-glycoprotein 6 . Results from in vitro studies on rats have indicated dose-dependent effects of silibinin on methadone metabolism, resulting in 50 to 100 percent reduction in methadone metabolism, which can lead to enhanced serotonin re-uptake inhibition and increased serotonin activity 7,8 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these data are also not in full agreement. Silymarin or silybin increased plasma the AUC and/or C max of the CYP3A4 substrates imatinib, ivabradine, methadone, paclitaxel, nitrendipine, and quinidine, but the AUC of another CYP3A4 substrate, trazodone, decreased, and no change in the CYP3A4 metabolism of amiodarone to desethylamiodarone was observed 123,249–255 . A more detailed look also finds a discrepancy between the suggested theory and results, for example, ivabradine is metabolized by CYP3A4 to desmethylivabradine.…”
Section: Interactionsmentioning
confidence: 92%